2018
DOI: 10.1371/journal.pone.0193514
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic bladder findings in patients with Congenital Zika Syndrome: A novel condition

Abstract: IntroductionCongenital Zika Syndrome (CZS) has been associated with microcephaly and other central nervous system abnormalities including areas that have been implicated in the control of the lower urinary tract. As such, this descriptive case series has aimed to investigate whether CZS is linked with neurogenic bladder. Identifying such an association is paramount in the effort to recognize CZS complications that have putative treatment options that could mitigate the impact of CZS in infected children.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 29 publications
4
34
0
2
Order By: Relevance
“…This syndrome is characterized by a broad spectrum of fetal changes, with microcephaly being the most striking, even if present only in part of the affected newborns (Petersen et al, 2016;Rasmussen et al, 2016;van der Eijk et al, 2016;Ministério da Saúde, 2017). Clinical consequences of CZS include the presence of pronounced brain damage and intracerebral calcification, cortical reduction, atrophy, cerebellar hypoplasia, arthrogryposis, ocular lesions, and neurogenic bladder (Chimelli et al, 2017;Honein et al, 2017;Costa Monteiro et al, 2018). In Brazil, 2865 cases of newborns and children with growth alterations and microcephaly caused by Zika infection during pregnancy were reported from November 8, 2015, to December 29, 2018, not counting those who died (Ministério da Saúde, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome is characterized by a broad spectrum of fetal changes, with microcephaly being the most striking, even if present only in part of the affected newborns (Petersen et al, 2016;Rasmussen et al, 2016;van der Eijk et al, 2016;Ministério da Saúde, 2017). Clinical consequences of CZS include the presence of pronounced brain damage and intracerebral calcification, cortical reduction, atrophy, cerebellar hypoplasia, arthrogryposis, ocular lesions, and neurogenic bladder (Chimelli et al, 2017;Honein et al, 2017;Costa Monteiro et al, 2018). In Brazil, 2865 cases of newborns and children with growth alterations and microcephaly caused by Zika infection during pregnancy were reported from November 8, 2015, to December 29, 2018, not counting those who died (Ministério da Saúde, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The strongest evidence for the neurotropic activity of ZIKV arises from prenatal exposure to the virus, which can lead to Congenital Zika Syndrome, one of the most severe manifestations being microcephaly [ 25 ]. Additional manifestations associated with congenital ZIKV infection that have been identified to date include epilepsy, motor abnormalities and bladder dysfunction [ 60 , 61 ]. While the exact mechanism for the neurotropic activity of ZIKV remains unclear, a suggested mechanism is through the virus’s ability to halt the proliferation of neural progenitor cells and possibly induce cell death [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, it could lead to recurrent urinary tract infections, urinary incontinence, and ultimately chronic and end-stage renal diseases. To the best of my knowledge, this is the first report that confirms a diagnosis of neurogenic bladder in infants with CZS [ 43 ]. The high incidence of neurogenic bladder observed in this study implies that all infants born with CZS should be screened for this condition in order to provide early treatment interventions to improve long-term clinical outcomes.…”
Section: Potential Long-term Impact Of Zikv Infection In the Kidneymentioning
confidence: 90%
“…Although I have observed full lytic replication of ZIKV in primary human glomerular cells in vitro, I have not encountered reports on immunocompetent patients having renal disease that is directly associated with ZIKV infection. However, a recent study by Costa-Monteiro et al reported on the development of neurogenic bladder in 21 pediatric patients with CZS [ 43 ]. All 21 patients clinically presented with an overactive bladder, with reduced bladder capacity and elevated detrusor pressure [ 43 ].…”
Section: Potential Long-term Impact Of Zikv Infection In the Kidneymentioning
confidence: 99%
See 1 more Smart Citation